Difusi Inovasi New Media Komunikasi pada Masyarakat Kampung Mosso di Perbatasan Indonesia-Papua New Guinea: Diffusion of New Media Communication Innovation in the Community of Mosso Village on the Indonesia-Papua New Guinea Border - Sulistiani, Indah; Syarifuddin, Syarifuddin; Rery, Samdar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The people of Mosso village live in the Indonesia-Papua New Guinea border area. Their daily activities include work hunting in the forest, gardening, and fishing in rivers. The economy of the Mosso community is classified as low, as is the level of education of the Mosso community in the low category. Access to information has yet to be available, so the community needs more knowledge to adapt to developments in the digital era, especially since communication networks in Mosso village will only be available at the beginning of 2023. This PKM activity aims to increase people's knowledge and skills in digital-based communication media through training activities on applying digital communication media to the community in Mosso village, Muara Tami District, Jayapura City. The activity was carried out in Mosso village, Muara Tami District, with 25 participants. Activities are carried out by delivering materials face-to-face at the residents' meeting hall by providing materials, training, and assistance to residents in implementing digital communication media. The results of the activity running smoothly can be explained that community members have gained sufficient knowledge about digital communication media and can improve community skills through the use of digital communication media to support community activities.